Manajemen Pengembangan Keterampilan Vokasional (Vocational Skills Development Management) Pendidikan Khusus (Studi Multi Situs Pada SLB-C Negeri Pembina dan SLB Negeri Kota Banjarbaru - Arfawi Arfawi; Aslamiah Aslamiah; A. Muhyani Rizalie (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to describe the management of special education vocational skills development. This research used a qualitative approach with a multi-site study design and data collection techniques through interviews, observation, and documentation. The sample in this study used purposive sampling. Data sources for this research include school principals, teachers, and education staff. Data analysis using descriptive analysis begins with data condensation, data presentation, and drawing and verifying conclusions. Meanwhile, the technique for checking the validity of the data is carried out through diligent observation and triangulation. The results of the research show that vocational skills development management is implemented by fulfilling the stages of the management function, which consist of planning, including analysis of community needs, formulation of the school's vision and mission, planning appropriate learning resources, planning to improve the quality and professionalism of teachers, funding planning, field planning facilities and infrastructure and forms of special service planning; organizing includes determining the organizational structure, placement of teachers and students, determining the position of skills education, allocating facilities and infrastructure; implementation of skills education is carried out through learning strategies, the role of teachers and partnerships with DUDI; control is carried out by conducting supervision, assessing learning outcomes and the quality of education (academic and non-academic). In conclusion, the management of vocational skills development at SLB-C Negeri Pembina Banjarbaru and SLB Negeri Banjarbaru City, namely the management that has been carried out, has been implemented. Keywords: Development Management, Special Education, Vocational Skills,